Origin of the spinel-pyroxene symplectites in the harzburgites from the New Caledonia Peridotite - Secchiari, Arianna; Montanini, Alessandra; Bosch, Delphine; Macera, Patrizia; Cluzel, Dominique (Ofioliti, 2019)
The New Caledonia ophiolite (Peridotite Nappe) hosts one of the largest and best-exposed mantle section worldwide, providing an exceptional insight into upper mantle processes. The Peridotite Nappe is mostly dominated by harzburgites, locally overlain by mafic-ultramafic cumulates, but also includes minor spinel and plagioclase lherzolites, cropping out in the northern part of the island. The New Caledonia harzburgites are low-strain tectonites, showing dominant porphyroclastic textures. The main mantle paragenesis is constituted by olivine ( 75-85 vol%), orthopyroxene ( 15-25 vol%) and spinel (< 1 vol%), while primary clinopyroxene is notably absent. An important textural feature of these mantle rocks is represented by the common occurrence of spinel-pyroxene symplectitic aggregates. In this work, we present a petrographical, textural and major element chemical characterization of the spinel-pyroxene symplectitic intergrowths occurring in the New Caledonia harzburgites (Kopeto, Central Massif, and Yaté, Massif du Sud). Based on textures, size and relationships with the other mineral phases, these spinel-pyroxene clusters have been divided into two types, named type-A and type-B. Type-A symplectites occur in the Kopeto harzburgites and are composed of spinel-orthopyroxene (± clinopyroxene) intergrowths. In type-A symplectites, symplectitic spinel (Spl2) occurs as abundant vermicular shaped grains, ranging in size from 0.5 to 2 mm. By contrast, spinel of the porphyroclastic assemblage (Spl1) shows smaller size (in the range of few m) and notably lower abundances (< 1%). Type-A symplectites develop exclusively on porphyroclastic olivine, which in turn displays evidence of chemical disequilibrium and corroded outlines. Bulk major element composition reconstructed for type-A symplectites rule out a derivation from a pre-existing garnet phase, as the model garnet compositions do not satisfy garnet stoichiometry, being characterized by Si deficiency. By contrast, major element chemical variations of the symplectitic phases, coupled with the high abundance of Spl2 and olivine resorption, suggest an origin from reactive percolation of opx-saturated hydrous melts or slab-derived fluids in a subduction zone setting. Type-B symplectites are found in Yaté sample and consist of spinel-orthopyroxene (± clinopyroxene). They are characterized by smaller size (few hundreds of m, i.e. “micro-symplectites”) and different shapes compared to type-A symplectites, growing as vermicular, “myrmekite-like” intergrowths at the rims of porphyroclastic orthopyroxene. Major element chemical compositions of type-B symplectites are consistent with an origin as “cooling textures”. These structures may derive from unmixing of a high-T, Al-Cr rich, orthopyroxene due to the decreased solubility of the Cr-Al component (CrMgTs) during post-melting lithospheric cooling at T < 900°C.